Atypical fibrous osteodystrophy in a lactating mare (Research, Society and Development, 2020)
Secondary nutritional hyperparathyroidism is a condition caused by increased serum phosphorus levels compared to calcium, which leads to an growth in the production of the PTH, parathyroid hormone of the parathyroid glands, increasing the osteoclastic activity withdrawing calcium from the bones, forming fibrous tissue, known as osteodystrophy, usually in the facial bones. The goal of this paper was to report an atypical case of hyperparathyroidism and fibrous osteodystrophy in a 8-year-old lactating mare, whose face enlargement was focal and nodular, involving of the right nostril and incisor bones, causing breathing and feeding difficulties. In the radiological examination the image was suggestive of osteosarcoma, with Doppler showing superficial circulation to the nodular mass. Treatment with cisplatin and calcium supplementation was performed. The the patient died three days after a temporary tracheostomy and a biopsy procedure. At necropsy parathyroid’s lymphadenomegaly was confirmed by histopathology, and osteodystrophy in the maxillary region was observed. In this case, hyperparathyroidism did not presented itself as a typical form, and there is a need for further studies on possible atypical forms of the disease on tropical countries.